Links between the Gantt Chart and Network Methods (CPM and PERT) - Anna GRZES (Communications of International Proceedings, 2021)
Introduction: In planning and controlling projects, many methods are used to increase the efficiency of their management. They come from a variety of disciplines, including management and operations research. In the literature, methods from these disciplines are often presented separately without showing the similarities and differences between them.  Objective: This article aims to show the links between the Gantt chart and network methods (i.e. CPM and PERT), to present the differences between them, and to determine the suitability of their application for managing the activities that constitute a project. Methodology: It will be used an example of a hypothetical project was developed, consisting of 15 activities, their duration, and the dependencies between them. Results: The application of these methods enabled calculation of the expected duration, the probability of shortening of this duration, and determination of critical paths. However, the Gantt chart is less accurate in determining the appropriate critical paths than the network methods. Conclusions: A comparison of these three methods leads to the conclusion that the input information necessary for the application of the network methods and Gantt chart are similar. CPM and PERT provide more detailed information on the course of the project and the consequences of possible delays, as well as the probability of shortening duration. However, the Gantt chart is easier to use in practice.
Keywords: Gantt chart; Critical Path Method (CPM); Program Evaluation and Review Technique (PERTh; planning and controlling of projects.